Mapping the impacts of multiple stressors on the decline in kelps along the coast of Victoria, Australia. (11th November 2022) - Young, Mary A.; Critchell, Kay; Miller, Adam D.; Treml, Eric A.; Sams, Michael; Carvalho, Rafael; Ierodiaconou, Daniel
Abstract: Aim: Kelp forests throughout temperate regions of the world serve as foundation species that play a critical role in sustaining the health and function of marine ecosystems but are experiencing declines in abundance due to a loss in resilience as the ocean climate changes. Ocean warming along southeast Australia has already been linked to dramatic losses of kelp species and is contributing to the range expansion and population increases of two species of sea urchin. This research attempts to understand the impact of multiple stressors on the decline in kelps in this region. Location: Coastal Waters of Victoria, Southeast Australia. Methods: In this study, we use long‐term (>20 years) datasets on biological observations across Victorian waters to determine trends in coverage and the impact of multiple environmental variables (oceanography, habitat, and urchin abundances) on two important kelps that serve as foundation species ( Phyllospora comosa and Ecklonia radiata) using boosted regression trees. These models were then used to develop predictive distribution models for each species and also to project abundance distributions into the future. Results: We found that both kelp species are decreasing in percent coverage over time with multiple environmental variables contributing to these declines, including increasing temperatures, intensifying wave energy, changes in currents and recruitment patterns, and increases in urchin populations. Additionally, future projections of temperature, wave energy, and urchin populations show that both species will continue to decrease across 62%–94% of their range by 2090. Main conclusions: Long‐term biological datasets allowed us to develop maps of the past, current, and future distributions of these important foundation species, providing valuable information to managers for prioritization of areas for targeted urchin management and restoration of kelps. Understanding the environmental factors affecting their distribution helps guide manager restoration investments in regions where kelp populations are most likely to persist in the future.